Coral reef fish abundance and diversity of seagrass beds in Kavaratti atoll, Lakshadweep, India - Vijayanand, P E; Pillai, N G K (Indian Journal of Fisheries, 2011)
The community organization of coral reef fishes in the seagrass sub-habitat ofKavaratti toll, Lakshadweep, India was studied during the period from January1991 to June 1992. Twenty-seven families represented by 65 species wererecorded by the visual censes method. The community diversity for families andspecies was 2.49 and 3.14 respectively. Juveniles and sub-adults of the mostadult reef fish, which inhabit other sub-habitats, were recorded here. The highspecies diversity in the seagrass beds is due to their roles as nurseries, shelterand foraging grounds for many species. Labridae, Chaetodontidae, Acanthuridaeand Mullidae were the most speciose families. Ocurrence of siganids was highlyseasonal. The cover that seagrass canopy provides conceals many species andperhaps influenced counts. The occurrence of balistids could be related to thepresence of interstitial and patches and abundant invertebrate food. Scorpaenidssubsisted on abundant invertebrates and juveniles fishes. High counts andpronounced variations make seagrass beds unstable habitats. However, monsoonassemblages were relatively stable perhaps due to lack of excessive new recruitsand a habitat shift by most species.